Immanuel Kant’s Critical Philosophy and Hermann Cohen’s Neo-Kantianism in Stanisław Leopold Brzozowski’s Reflection - Musioł, Anna Agnieszka (Folia Philosophica, 2018)
In the article, I want to describe the place of Immanuel Kant and Hermann Cohen’s Neo-Kantianism in the thought of Stanisław L. Brzozowski philosophy. So the critical image of philosophy is showing the project of Kant, so the concept of Cohen is — how Brzozowski thinks — with an expression of truly independent reflection. In the system of Cohen, author Legenda Młodej Polski…, a tendency to intellectual initiative free from positivist and modernist restrictions notices. How the history of philosophy is showing, both favored German classics of transcendental method, freedoms treat the criticism as a contemporary concept and innovative original thought. Meanwhile, for Brzozowski, criticism is an opportunity for including the philosophy of Kant into the form of the summons to the creative bravery, and it all at the same time is also Marburg doctrine, in accordance which is an existence missing apart from becoming eternal and ceaseless (eternal fieri).